UJI TOKSISITAS AKUT LD50 CAMPURAN EKSTRAK DAUN BIDARA ARAB (Ziziphus spina-christi L.) dan DAUN SAGA POHON (Adenanthera pavonina) - Dinda Enka Nita; Ersalina Nidianti; Khoirul Ngibad; Suprapto Maat; Bismi Aisyah Rahma Putri (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
The mixture of Arabian bidara leaf extract (Ziziphus spina-christi L.) and saga tree leaves (Adenanthera pavonina) is a plant used by the community which is empirically used as a traditional medicine such as hyperlipidemia and hypercholesterolemia. The purpose of mixing these two extracts is to increase the efficacy of both extracts which are rich in antioxidants. However, a study on the acute toxicity test of the use of the mixture of these plants has not been carried out, so an acute toxicity test is needed on both extracts to see the safety of use. The purpose of this study was to determine the symptoms of toxicity and the LD50 value caused after the fusion of 56 male and female Wistar strain white rats (28 males, 28 females) which were then divided into 7 groups. The negative control group was not treated, the carrier control group was given a suspension of 1% Na CMC at a dose of 0 mg/Kg given distilled water and the treatment group was given a mixture of Arabic bidara leaf extract and saga tree leaves 1:1 at a dose of 2000 mg/KgBB, 4000 mg/KgBB, 6000 mg/KgBB, 8000 mg/KgBB, oral sonde was performed once a day then observed after 24 hours for 14 days by looking at the number of deaths and symptoms of toxicity. The results obtained were that the mice experienced symptoms of toxicity, weakness, palpitations and decreased activity, with LD50 in male mice of 4224.511 mg/KgBB, in female mice 3030.354 mg/KgBB categorized as slightly toxic.